LEGAL POLICY ON SEXUAL HARASSMENT (CATCALLING) FROM THE PERSPECTIVE OF CRIMINAL LAW - Wily Novan Prakoso; Firman Halawa (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This article aims to understand and analyze the regulation of catcalling from a criminal law perspective as well as analyzing the regulation of verbal sexual harassment according to criminal law reform. This research is normative legal research. The results of this research are that the act (catcalling) has the potential to be a criminal act that meets the elements of a criminal act, this act is categorized as an act of verbal sexual harassment and can be studied from several articles in the Criminal Code, the Law on pornography and the need for a legal policy. related to special rules for the act of catcalling to achieve legal certainty and also the fulfillment of criminalization conditions so that the act of catcalling can be specifically regulated. The conclusion is that the act of catcalling has the potential to be a criminal act that occurs in the public sphere through the elements of a criminal act, the impact of this act of catcalling results in mental and psychological disorders, up to the psychological level and to determine a policy it is necessary to pay attention to the morals, values ​​and principles contained in it. in society and pay attention to the conditions of criminalization. To achieve legal certainty, there is a need for legal policies regarding regulations specifically related to catcalling as well as social sanctions for catcalling perpetrators